2018
DOI: 10.12816/0044748
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students' Beliefs and Attitudes towards Schizophrenia before and after Psychiatric Training in Almaarefa Colleges, Riyadh, Saudi Arabia

Abstract: Background: Public surveys have shown that the general population has limited knowledge about mental illness and holds unfavorable attitudes towards the people who suffer from it in various, culturally diverse, countries. Aims: The aim of the present study was to explore medical students" beliefs and attitudes towards people with schizophrenia (PwS) prior to receiving any training in psychiatry and to assess the impact of the psychiatric placement on changing them. Methods: A questionnaire addressing beliefs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…The study suggests slight positive changes were apparent to perceptions towards social distance, but these seemed to then decline at a one-month follow up. Moreover, studies focusing on medical students in a psychiatric placement with the exception of De Witt et al (2019) revealed an increase in stigmatising attitudes (Economou et al , 2012; Alhajri and Alghamdi, 2018). Economou et al (2012) found negativity to be notable in relation to beliefs about “dangerousness” and variables associated with gender appeared to also have some bearing, as female participants seemed to harbour greater negative attitudes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study suggests slight positive changes were apparent to perceptions towards social distance, but these seemed to then decline at a one-month follow up. Moreover, studies focusing on medical students in a psychiatric placement with the exception of De Witt et al (2019) revealed an increase in stigmatising attitudes (Economou et al , 2012; Alhajri and Alghamdi, 2018). Economou et al (2012) found negativity to be notable in relation to beliefs about “dangerousness” and variables associated with gender appeared to also have some bearing, as female participants seemed to harbour greater negative attitudes.…”
Section: Resultsmentioning
confidence: 99%
“…The study by Roberts et al (2008) indicated single education sessions did not appear to influence student attitudes. Whilst acknowledging the changes in attitudes, the long term and temporal implications for change need to be considered (Bharathy et al , 2016; Burns et al , 2017; Alhajri and Alghamdi, 2018). However, the more recent study by Ma and Hseih (2020) indicated the positive effects remained for one year after the training was completed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the Saudi context, medical students were found to either maintain or increase their desire for social distance from psychiatric practice after placement in contact with schizophrenia cases (Alhajri & Alghamdi, 2018). These findings may suggest that aspects of students’ beliefs or experiences before or during their placement are counterproductive to improving their acceptance of pursuing mental health as a field of practice.…”
Section: Discussionmentioning
confidence: 99%
“…Situasi kondusif yang mendukung kepercayaan diri mahasiswa, pendekatan holistik tentang masalah psikiatri, serta pemahaman tentang keterkaitan psikiatri dengan ilmu lain ini pada akhirnya dapat berperan dalam destigmatisasi mahasiswa. Hal ini senada dengan Alhajri & Alghamdi (2018) yang menyebutkan bahwa situasi pembelajaran yang kondusif dan berorientasi anti-stigma dapat membantu mahasiswa untuk lebih dapat menghargai masalah kesehatan jiwa baik secara personal maupun profesional (Alhajri & Alghamdi, 2018). Penekanan penggunaan prinsip-prinsip neurosains dalam menjelaskan kasuskasus Psikiatri juga dapat mendukung proses destigmatisasi karena pendekatan ini membantu mahasiswa untuk memahami masalah Psikiatri sebagai masalah medis sebagaimana penyakit lainnya dan menurunkan kesan 'asing' dan 'aneh' dari Psikiatri (Porter-Stransky & Gallimore, 2022).…”
Section: Pembahasanunclassified